Analisis Tindakan Passing Off Terhadap Merek Terkenal (Well-Known Mark) dalam Perspektif Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Dita Saraswati; Wilma Silalahi (Jurnal Hukum Lex Generalis, 2024)
The trade of products bearing well-known marks often encounters various issues, primarily arising from acts of passing off perpetrated by business actors acting in bad faith. Well-known marks, which enjoy a strong reputation, are frequently exploited by irresponsible parties seeking to boost sales and profit from the unauthorized use of such marks. However, such practices can cause significant harm to the owners of well-known marks by misleading the public and damaging the reputation that the marks have painstakingly built over time. In this context, this legal research adopts a normative legal approach, also known as doctrinal legal research, which focuses on the study of literature and secondary legal materials, including both primary and secondary legal sources. Based on the findings of the research, the regulation of trademarks in Indonesia is clearly stipulated in Trademarks and Geographical Indications Act. One of the preventive measures to address acts of passing off against well-known marks is the registration of the mark through a formal application process, which grants legal protection to the mark in accordance with the provisions of Trademarks and Geographical Indications Act. With valid trademark registration, passing off actions against well-known marks can be deterred, as the registered marks enjoy stronger legal protection. Owners of registered well-known marks are entitled to file lawsuits in the Commercial Court against parties that use similar marks without authorization or legitimate rights, whether for goods or services of a similar nature or otherwise. This is aimed at safeguarding the interests of well-known mark owners from potential losses caused by trademark infringements. Lawsuits brought by the owners of well-known marks may include various legal claims, such as claims for damages and requests for injunctions to cease activities related to the trademark infringement. The conclusion of this research indicates that passing off arises from the bad faith of business actors who are solely focused on profit-seeking motives.